Pengaruh Layanan Daring Perpustakaan Perguruan Tinggi Negeri Badan Hukum Selama Pandemi Covid-19 terhadap Minat dan Perilaku Penggunaan Ulang Mahasiswa Tingkat Sarjana - Muhammad Rosyihan Hendrawan; Kurniasih Yuni Pratiwi (Media Pustakawan, 2023)
The impact of information technology (IT) advances in recent years has seen widespread growth in the use of different approaches in academic libraries. Its implications create a global effect on making it efficient in supporting digital transformation, including providing online services. Online services during the COVID-19 Pandemic are the best and most innovative strategic support facilities that have been built and developed by the Brawijaya University Library and the Airlangga University Library, which are included in the Legal Entity State University (PTN BH) in East Java Province, Indonesia. This study uses the Unified Theory of Acceptance and Use of Technology 3 (UTAUT3) Model in IT as a potential determinant of acceptance and use of online services by undergraduate students at both institutions, especially during the Pandemic. This study aims to analyze the online services of the Brawijaya University Library with Remote Xs and the Airlangga University Library with E-Resource Services and find a comparison of the two based on the UTAUT3 Model. Based on the results of research on online services from both academic libraries, it was found that aspects of interest in online services were found, and there was a commitment by undergraduate students to use them again in the following semester. Undergraduate students highly recommended the online services of each academic library to their colleagues because of a positive perception of these services. The behavioral aspect of reusing online services at the Brawijaya University Library is relatively high, but on the contrary, at Airlangga University Library.